ANALYSIS OF THE DEPENDENCE OF THE FLEXIBILITY AND PHYSICAL MECHANICAL PROPERTIES OF COTTON FIBER YARN ON THE DRAWING RATE - F. A. Kozakov; D. G. Aliyeva; R. Karimov; A. A. Murodillayev (Modern American Journals, 2025)
In this research work, the effect of the length of samples of yarns spun from cotton fiber with a linear density of Nm-34/1 on their mechanical properties was determined by breaking them in a semi-periodic manner on a YG026T device. Based on the determined values, the elasticity of the yarn was calculated using a formula and the results are presented in graphical form.
Keywords: Elongation, relative breaking strength, breaking strength, spun yarn, speed, deformation, yarn thickness, strength, structure, moisture, elasticity, speed, tension, elongation at break, elastic deformation.